Wide Resection and Iliac Crest Arthrodesis for Multiply Recurrent Giant Cell Tumor of First Metatarsal - Andrew Golz; Michael Murphy; Lukas Nystrom; Adam Schiff (Case Reports in Orthopedics)
Case. Giant cell tumor of bone is a benign, aggressive neoplasm commonly arising in the femur, tibia, and distal radius and less commonly in the hands and feet. We describe a 22-year-old woman who underwent wide resection of multiply recurrent first metatarsal giant cell tumor and reconstruction with iliac crest arthrodesis. Conclusion. To our knowledge, there have been no previous reports of managing multiply recurrent giant cell tumor of the first metatarsal. The patient was without pain and exercising without difficulty 18 months following surgery. This method appears useful for reconstructing the foot following multiply recurrent giant cell tumor of the metatarsal.